A Facile Potential-Induced In-Situ Ion Removal Trick: Fabrication of High-Selective Ion-Imprinted Film for Trivalent Yttrium Ion Separation. (10th September 2015) - Du, Xiao; Sun, Xiaolong; Zhang, Hao; Wang, Zhongde; Hao, Xiaogang; Guan, Guoqing; Abudula, Abuliti
Graphical abstract: Highlights: Y 3+ ion imprinted FCN/PPy film was fabricated successfully by using UPEP method. The resulting Y 3+ -FCN/PPy film shows excellent ESIX performance for Y 3+ ion. A complicated Y 3+ ion exchange process in different E-IIPs is studied by EQCM. Two distinct stages during the adsorption process of Y 3+ into the E-IIPs are characterized. ABSTRACT: A novel electroactive trivalent yttrium ions imprinted polymer film composed of ferricyanide embedded conductive polypyrrole (FCN/PPy) is fabricated by using a facile unipolar pulse electropolymerization (UPEP) method. The imprinted Y 3+ ions can be removed in situ from the growing film by tactfully inducing potential oscillation on the film electrode based on the electric repulsion. Cyclic Voltammetry (CV) measurements combined with Electrochemical Quartz Crystal Microbalance (EQCM) are applied to characterize quantitatively the electrochemical uptake/release process of Y 3+ ions in various electroactive ions imprinted polymer films (E-IIPs), including non-ion, divalent nickel ion and trivalent yttrium ion imprinted FCN/PPy composite films. It is found that the reversible uptake/release of Y 3+ ions can be realized by simply regulating the operating potential applied to the Y 3+ ions imprinted composite film electrode in aqueous solution of 0.1 mol L −1 Y(NO3 )3 due to the unique Y 3+ ion identification capability of ion imprinted cavity and the dual driving forces resulting from both PPy and FCN. From the electrode mass change of different E-IIPs, one can speculate that parts of bound water molecules around the hydrated Y 3+ ions could move into the E-IIPs with the ions adsorption process. Two distinct stages, the adsorption of Y 3+ ions at the surface layer of E-IIPs and the transport of adsorbed ions to inner layer of E-IIPs, should be involved in the adsorption process of Y 3+ ions into the E-IIPs. For hydrated Y 3+ ions adsorbed electrochemically into the surface layer of Ni 2+ -imprinted and Y 3+ -imprinted FCN/PPy composite films, the numbers of bound water molecules with Y 3+ ions are estimated to be 1 and 4.6, respectively. It suggests that the Y 3+ ion exchange performance in E-IIPs significantly depends on the size of ion cavity and the stereochemistry of binding sites.